Jeff Corwin : a wild life : the authorized biography - Corwin, Jeff (Puffin Books, 2009)
Based on extensive research and one-on-one interviews with Jeff, kids will get an honest telling of the incredible journey of the popular Animal Planet host from child nature enthusiast to naturalist and animal specialist.